Núcleo de reflexão e ressocialização para autores de violência doméstica: ponte para efetividade da proteção à mulher - Sousa, Elias Pereira (Universidade Federal do Tocantins, 2018)
This is a propositional dissertation which purpose is to suggest the implantation of a Reflection and Resocialization Nucleus to authors of domestic violence as a bridge for effectiveness on women protection. In order to do so, a study was made and it was about the historical context of social and cultural factors that contributed to the educational process of men, the strive and achievements of women for their rights from the colonial period to the current days, such as freedom of expression and human dignity, culminating in one of the main achievements in the fight against domestic violence – the creation of the Maria da Penha Law – which brought, in addition to emergency protective measures in the disfavor of the agressor, other measures that turned out to be an Assistance Network for women, and consequently, for men. This study is justified because of its importance to the State of Tocantins Court of Justice and to the author of this research as a legal professional, and to society, once the high rate of violence against women in the State of Tocantins, indicated by statistics, points the State Nationwide as second in the ranking, and the Capital Palmas as first in the theme domestic violence. For the project, a positivist method was used for being more suitable to the proposal, seeking to verify the reality of the facts and data extracted from researches carried out by Justice agencies, as well as the empirical research. The results indicate that the regions in Brazil in which Reflection and Resocialization Nucleus were implanted, there were positive results, with a recurrence rate reaching zero, confirming that for a true change of thinking, transformation, men must undergo a re-education process, that, for the present case, will come from meetings in the Nucleus that follow as a suggestion for the domestic conflicts solution in the State.